1986
DOI: 10.1557/jmr.1986.0144
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond resolution time-resolved x-ray study of silicon during pulsed-laser irradiation

Abstract: We have used the pulsed time structure of the Cornell High-Energy Synchrotron Source (CHESS) to carry out a nanosecond resolution time-resolved x-ray study of silicon during pulsed-laser irradiation. Time-resolved temperature distributions and interfacial overheating and undercooling were measured on 〈111〉 and 〈100〉 silicon during 25 ns UV laser pulses through the analysis of thermal expansion induced strain. The temperature gradients were found to be > 107 K/cm at the liquid-solid interface and the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…The variations of q * | x * =0 with respect to the time which are obtained from equation (5.6), the ballistic-diffusive equations (Chen 2001(Chen , 2002 and the Fourier law, are displayed in figure 2 (the horizontal axis is for the logarithm of time to base 10) for the case Kn = 10.0. One can see that the non-dimensional heat flux at the boundary x * = 0 expressed by equation (5.6) is lower than the result obtained by the classical heat conduction equation, which agrees with the experimental observation (Larson et al 1986). In comparison with the result obtained by Chen (2001Chen ( , 2002, our result is larger at earlier time and smaller at later time.…”
Section: A One-dimensional Heat Conduction Problemsupporting
confidence: 90%
“…The variations of q * | x * =0 with respect to the time which are obtained from equation (5.6), the ballistic-diffusive equations (Chen 2001(Chen , 2002 and the Fourier law, are displayed in figure 2 (the horizontal axis is for the logarithm of time to base 10) for the case Kn = 10.0. One can see that the non-dimensional heat flux at the boundary x * = 0 expressed by equation (5.6) is lower than the result obtained by the classical heat conduction equation, which agrees with the experimental observation (Larson et al 1986). In comparison with the result obtained by Chen (2001Chen ( , 2002, our result is larger at earlier time and smaller at later time.…”
Section: A One-dimensional Heat Conduction Problemsupporting
confidence: 90%
“…The undercooling was also found to be orientation and regrowth velocity dependent: ∼5 K/m s on (100)Ge and ∼20 K/m s on (111)Ge. 23,24 Basharin et al 16 have estimated the temperature dependence of Gibbs free energy of graphite, metastable liquid carbon and diamond at a low pressure of 120 MPa of helium and found that free energy of liquid carbon can be equal to that of diamond at 4160 ± 50 K, which is considerably lower than melting point of liquid graphite, at a pressure of 120 MPa of helium. Thus, it is possible that diamond can be nucleated from super undercooled state at 4160 K. However, Basharin et al 17 tried to quench diamond using 1-ms pulsed laser melting (wavelength of λ = 1.06 µm and a power of 10 kW) of HOPG graphite with limited success due to lower undercooling with 1 ms lasers on a crystalline graphite substrate.…”
Section: -21mentioning
confidence: 99%
“…Undercooling during nanosecond laser (KrF laser λ = 0.248 µm) melting has been measured in crystalline Ge and Si using nanosecond resolution time-resolved x-ray diffraction in a synchrotron. 25,26 These results showed undercooling as high as 110 ± 30 K on (111) Si during ∼10 ms −1 melting and ∼6 ms −1 regrowth velocity. Thus, the undercooling is crystalline Ge and Si is roughly half that predicted theoretically for amorphous Ge and Si.…”
Section: Boron Nitride (Bn) Exists In Four Polymorphs Namely Hexagomentioning
confidence: 72%